PENGEMBANGAN LKPD BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN KOLABORASI PESERTA DIDIK SEKOLAH DASAR PADA MATERI PENGOLAHAN DATA - Putri, Ade Bagus; Rohman, Fatkhur; Marcheila, Lovita; Nurhanurawati; Damayanti, Trisya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop and test the effectiveness of the Student Worksheet (LKPD) based on Problem Based Learning (PBL) in improving students' collaboration skills in data processing material at SD Negeri 1 Waydadi, Sukarame District, Bandar Lampung City. The study uses the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The developed LKPD was validated by experts in content, language, and graphic design, and then tested in the classroom with 5 students. The effectiveness evaluation was conducted using the N-gain test to measure changes in collaboration skills before and after the implementation of the LKPD. The results show that the PBL-based LKPD is effective in improving students' collaboration skills, with an N-gain value of 81.4%, which falls into the high category. Although there are challenges in the equitable distribution of tasks and communication among group members, overall, this LKPD has proven to be practical and effective for use in learning to enhance students' collaboration skills.